Calorimetric Study of Inulin as Cryo- and Lyoprotector of Bovine Plasma Proteins - Rodriguez Furlán, Laura Teresa (2013)
Inulin is a generic term applied to heterogeneous blends of fructo-oligosaccharides which are reserve carbohydrate sources present in many plant foods such as bananas,onions, garlic, leeks, artichokes and chicory, which represents the main commercial source.This polysaccharide has a wide range of both, nutritional and technological applications.Nutritionally, inulin is regarded as a soluble fiber which promotes the growth of intestinalbacteria, acting as a prebiotic. Also, is a non-digestible carbohydrate with minimal impact on blood sugar and unlike fructose, it is not insulemic and does not raise triglycerides being generally considered suitable for diabetics and potentially helpful in managing blood sugarrelated illnesses . Among the technological benefits, inulin is used as fat and sugar replacement, low caloric bulking agent, texturing and water-binding agent . One general property of the saccharides is the stabilization of proteins by their incorporation into carbohydrate solutions before freeze-drying being this a known preservation procedure. The previous incorporation of saccharide promotes the formation of amorphous, glassy systems, inhibits crystallization and influences the kinetics of deteriorative reactions upon storage by which its structured integrity is maintained . To act successfully as a protectant, the saccharides should have a high glass transition temperature (Tg), a poor hygroscopicity, a low crystallization rate, containing no reducing groups. When freezedrying is envisaged as a method of drying, a relatively high T´g of the freeze concentrated fraction is preferable. Previous studies demonstrated that inulin meets these requirements being excellent protector of therapeutical proteins and viruses over the drying and storage processes .The glass transition temperatures of the maximally concentrated frozen solutions (T´g) wereanalyzed and compared to the experimental results by applying the predictive equations of Miller/Fox and Gordon/Taylor extended for multi-component systems. The glass transition (Tg) of the freeze dried multi-component mixtures, the onset crystallization temperature (Tc) of the solute at temperatures above Tg, in the freeze dried samples were determined.Furthermore, the kinetics of the denaturation and the thermal denaturation (Td) of the freeze-dried samples, at different DSC scan rates, protein concentrations and pH, were analyzed and the thermodynamic compatibility of the different matrix components were determined. The enthalpy change involved in the denaturation reactions of proteins was also determined. A kinetic model that describes bovine plasma proteins denaturation was proposed.